COMPETITIVE ADVANTAGE, DIGITAL MARKETING AND OMAN RECOVERY TOURISM PERFORMANCE: A CONCEPTUAL FRAMEWORK - Salina Rasli; Wafa Talib Al Hosni; Setyawan Widyarto (International Journal of Accounting, Finance and Business, 2022)
Due to covid-19 pandemic as like as other countries the Sultanate of Oman tourism also faced similar challenges to recovery and prosperity of domestic as well as international tourism. Once, it was being observed that its tourism potential, biological diversity, variation in weather from one governorate to another, throughout the year, and the presence of beautiful nature, golden sands, green mountains, clean beaches, quiet pristine areas, beautiful oases, castles, forts, and other components are quite reputed and attractive attractions for tourism in Sultanate of Oman. Therefore, the present study examined the existing available literature resources to develop the best conceptual model to justify the mediating effect of competitive advantage on the relationship between digital marketing dimensions (content, email, social media, search engine optimization (SEO) pay-per-click (PPC) advertising) and recovery performance Tourism in Oman. The summary review findings revealed the gaps of knowledge through the course of the relationship between Digital marketing and recovery tourism performance recovery as well as competitive advantage as a mediating means. The study also identified based on previous studies on the performance, competitiveness, and orientation of companies as we the researchers have seen from modern e-marketing according to the unbound theory, Porter's concept of comparative advantage, the theories of institutional and organizational culture based on services, tourism theory and behavior theory. Based on above findings, the present study develops a conceptual framework to justify the mediating effect of competitive advantage on the relationship between digital marketing dimensions (content, email, social media, search engine optimization (SEO) pay-per-click (PPC) advertising) and Recovery Performance Tourism (RTP) in Oman. The study recommends to justify this conceptual framework by empirical data from the tourism sectors and draw a policy guideline for ensuring for Recovery Performance Tourism (RTP) in Oman.